2011
DOI: 10.1177/1557988311416495
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer in Men

Abstract: Purpose. The aim of this study was to review the clinical presentation and to evaluate prognostic factors, treatment modalities, outcome, and second malignancy in male breast cancer patients. A chart review was conducted of all men treated for breast cancer between January 1991 and December 2007. Cox proportional hazards regression model and Kaplan-Meier curve were used to determine prognostic factors and plot survival probabilities. Invasive carcinoma was diagnosed in 22 patients and ductal carcinoma in situ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…Breast cancer has similar prognostic factors and behaviour in men and women [12] [168], which means that a higher degree of differentiation of the tumour is associated with a poorer prognosis; 2) Clinical cancer stage [40] [87] [167]- [169] i.e. tumours at higher stages produce a worse prognosis; 3) The hormone receptor status [10] [174], which means that larger tumours are correlated with shorter 5-year survival rates ( Table 3); 5) The most documented factor i.e.…”
Section: Prognostic Factorsmentioning
confidence: 99%
“…Breast cancer has similar prognostic factors and behaviour in men and women [12] [168], which means that a higher degree of differentiation of the tumour is associated with a poorer prognosis; 2) Clinical cancer stage [40] [87] [167]- [169] i.e. tumours at higher stages produce a worse prognosis; 3) The hormone receptor status [10] [174], which means that larger tumours are correlated with shorter 5-year survival rates ( Table 3); 5) The most documented factor i.e.…”
Section: Prognostic Factorsmentioning
confidence: 99%
“…In rich countries which are better organized and equipped, patients enjoy a well codified set of treatments. For example, in the USA, patients of Akkamma’s series were treated with surgery (95%), chemotherapy (54.5%), hormonal therapy (61%), and radiation therapy (34%) [ 9 ]. In France, in Oger’s series, patients were also treated by surgery (98%), chemotherapy (37%), hormonal therapy (92%), and radiation therapy (75%) [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the surgery of male breast cancer has become less and less invasive. The most recent studies mention lumpectomy and sentinel lymph node technique which give the same therapeutic results as radical surgery for tumors with sizes T1 and T2 [ 9 , 18 , 27 , 28 ]. The sentinel lymph node technique would enable like in women, reduce morbidity related to axillary dissection for small tumors of less than 2.5 cm [ 7 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While studies have suggested men's survival from breast cancer is poorer than women's, when adjustment is made for stage at presentation and age men fare as well or even slightly better [2,8,9]. Men tend to present at a later stage of disease [10] and are more likely to undergo mastectomy (74% versus 19% breast-conserving therapy (BCT)) [11]. This tendency to delayed presentation is attributed to lower perceived risk of cancer, symptoms other than a lump, and presentations are often precipitated by an appointment for an unrelated condition or by instruction to seek help by a relative or partner [12].…”
Section: Male Breast Cancermentioning
confidence: 99%